2014
DOI: 10.1055/s-0033-1363839
|View full text |Cite
|
Sign up to set email alerts
|

Role of Percutaneous Needle Biopsy for Renal Masses

Abstract: The role of percutaneous renal mass biopsy has expanded considerably in the past 10 years. The incidence of incidentally detected small (< 4 cm) solid renal masses is on the rise, and despite a commensurate increase in nephron-sparing treatment, the mortality rate from renal cell carcinoma remains the same. Earlier detection and treatment have not had dramatic effects on population outcome, implying that not all small renal masses will grow to be life-limiting. Indeed, many small solid renal masses are benign,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…1,5,7,9 With increasing expertise in biopsy performance and the understanding that not all renal masses are malignant and needing invasive measures (such as ablation or nephrectomy), the role of percutaneous biopsy has been on the rise. [1][2][3]5,6 Moreover, recent assessments of safety of renal mass biopsies state that the overall complication rates range from 1.4-4.7%, with major complications reported only in 0.46% of all patients undergoing renal mass biopsies. In particular, the most feared risk of tumour tract seeding has been estimated to be <0.01% with only eight total reported cases in literature to date.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,5,7,9 With increasing expertise in biopsy performance and the understanding that not all renal masses are malignant and needing invasive measures (such as ablation or nephrectomy), the role of percutaneous biopsy has been on the rise. [1][2][3]5,6 Moreover, recent assessments of safety of renal mass biopsies state that the overall complication rates range from 1.4-4.7%, with major complications reported only in 0.46% of all patients undergoing renal mass biopsies. In particular, the most feared risk of tumour tract seeding has been estimated to be <0.01% with only eight total reported cases in literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] One study estimates that up to 66% of RCCs are detected incidentally. 7 Importantly, not all incidentally detected renal masses on imaging are RCC or malignant in nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 There debate on the value of renal mass biopsy ranges having a high diagnostic yield to the optimal use is yet to be determined. 27,28 It should be noted that 2 separate studies of renal mass biopsy results found that about 80% were of diagnostic value while the remaining 20% were non-diagnostic. 18,29 Nevertheless, the sensitivity and specificity of AQP1 and PLIN2 for RCC versus other renal masses supports their analytical and clinical validity, and their potential application in the differential diagnosis and further evaluation of incidentally identified renal masses.…”
Section: Discussionmentioning
confidence: 99%
“…However, renal mass biopsy has been shown to be safe and clinically useful, particularly in the assessment of small renal masses. 1 The diagnostic rate of CT-guided renal mass biopsy has been shown to be in the region of 80e90%, and this technique has a superior diagnostic accuracy to fine needle aspiration cytology. As well as being useful in confirming the diagnosis and classification of malignant tumours, renal core biopsy can detect benign lesions such as renal oncocytoma and angiomyolipoma.…”
Section: Tumours Of the Kidneymentioning
confidence: 99%